Diversity of Scleria (Cyperaceae) in Santa Catarina, Brazil - Regina Affonso; Ana Zanin; Neil Alistair Brummitt (Rodriguésia)
Abstract Scleria is the fifth largest genus of Cyperaceae, and the third most diverse genus of Cyperaceae in Brazil. In Santa Catarina the floristic account of Cyperaceae is in need of updating, particularly as the Atlantic forest, home to many species of Scleria, is one of the most threatened environments worldwide. Scleria is thus a leading candidate for an updated floristic account, particularly so as to identify the conservation status of its species within the remaining natural vegetation. The survey has confirmed thirteen taxa including a new subspecies, S. georgiana ssp. australis, here described. Scleria sellowiana is lectotypified here. A species identification key, morphological descriptions, geographic distributions, global conservation status according to IUCN Red List criteria, habitats, phenological aspects, taxonomic notes and illustrations are provided for each species.